Effect of platelet-rich plasma treatment on antioxidant enzymes’ activity following hamstring injury among Malaysian athletes - Lai, Lingling; Mohd Nahar Azmi Mohamed,; Mohamed Razif Mohamed Ali,; Khong, Teng-Keen; Ashril Yusof, (Penerbit Universiti Kebangsaan Malaysia, 2016)
The objective of the present preliminary study was to investigate the effect of platelet-rich plasma (PRP) treatment alongside rehabilitation programme compared with rehabilitation programme alone on antioxidant enzymes’ (superoxide dismutase, SOD; catalase, CAT) activity and time to return to play (RTP) following hamstring injury among Malaysian athletes. Participants diagnosed with grade-2 acute hamstring injury (n=10) were randomised into 2 groups of PRP treatment and rehabilitation programme (PRP-T) and rehabilitation programme alone (CON). Blood samples were collected at baseline and 2 fortnightly (week-2, W2; week-4, W4) for the biochemical assessments. Participants were certified to have recovered upon fulfilling RTP criteria. PRP-T group showed a significantly lower CAT activity compared to CON group (47.55% lower at W2, 37% lower at W4, p<0.05), while there was no significant difference in SOD activity between the groups. Although PRP-T group benefited from an earlier (~15 days) time to RTP compared to the CON group, no statistically significant difference was noted; however, the effect size was large (Cohen’s d=0.9). These findings suggested that PRP treatment alongside rehabilitation potentially reduces the degree of secondary tissue damage and facilitates muscle recovery through regulation of antioxidant enzymes, which subsequently hastens time to RTP. Athletes and coaches could consider PRP as viable treatment for hamstring injury.